Scientific Theoretical Bases of Studying the Development of Creative Thinking in Preschool Children - Oripova Munisa Shamsiddinovna (Researchparks Publishing, 2023)
The article examines the scientific theoretical basis and specific features of studying the development of creative thinking in preschool children, and the pedagogical conditions that help such development are shown.